A adaptação de Comunidade Ribeirinha às novas tecnologias: a Energia Solar Fotovoltaica - BARBOSA, Geize Cristina Vidal de Sá (2024)
The extension work "The Adaptation of a Riverine Community to New Technologies: Photovoltaic Solar Energy", which includes the work plan linked to the extension project: The Presentation of Quantum Physics as a Gateway to Academic Entry, had the primary objective of exploring the perceptions, experiences and knowledge of riverside families about solar energy. The first stage included a bibliographic study on the topic and subsequently a selection of 20 family representatives from the community on the island of Urubuoca -Icoaraci-Outeiro/Belém-PA. This ensured a representative sample that reflects the diversity of perspectives and experiences present in the community. Qualitative and quantitative interviews were then carried out, adopting a flexible approach that allowed for in-depth exploration. The interviews covered essential topics, such as families' prior knowledge about solar energy, their perceptions regarding the technology and experiences with electricity in the community. Crucial issues, including access to electricity, specific energy needs and expectations for solar energy, were thoroughly investigated. The project is committed to comprehensively understanding the local context, identifying not only the demands, but also the advantages of solar energy for riverside communities. This open approach provided a solid foundation for obtaining important information that can guide future solar-related initiatives in these communities. In summary, the project achieved its objective, and also developed a thoughtful approach, ensuring that the voices of riverside families and their specific needs were heard. Those found are an important resource for developing sustainable energy solutions that benefit these communities significantly.